Pre-Existing Cross-Reactive Antibody Responses Do Not Significantly Impact Inactivated COVID-19 Vaccine-Induced Neutralization - Wang, Jin; Guo, Cheng; Cai, Lin; Liao, Conghui; Yi, Huaimin; Li, Qianlin; Hu, Huan; Deng, Qiang; Lu, Yuying; Guo, Zhongmin; Chen, Zeliang; Lu, Jiahai (Frontiers in Immunology, 2021)
Recent exposure to seasonal coronaviruses (sCoVs) may stimulate cross-reactive antibody responses against SARS-CoV-2. Previous studies have shown divergent results regarding protective or damaging immunity induced by prior exposure to sCoVs. It is still unknown whether pre-existing humoral immunity may play a role in the vaccine-induced neutralization and antibody responses. In this study, we collected 36 paired sera in healthy volunteers before and after immunization with inactivated SARS-CoV-2 vaccines, and analyzed the distribution and intensity of pre-existing antibody responses at the epitope level before vaccine immunization, as well as the relationship between pre-existing sCoVs immunity and vaccine-induced neutralization. We observed large amounts of pre-existing cross-reactive antibodies in the conserved regions among sCoVs, especially the S2 subunit. Except for few peptides, there were no significant differences in IgG and IgM fluorescence intensities against S, M and N peptides in pre-vaccination sera from the vaccinated people who developed a neutralization inhibition rate (%inhibition) <40 and %inhibition ≥40 after two doses of the COVID-19 vaccine. The subjects with strong and weak pre-existing cross-reactive antibodies (Strong pre-CRA; Weak pre-CRA) had similar %inhibition pre-vaccination (10.9%±2.9% vs. 12.0%±2.2%, P=0.990) as well as post-vaccination (43.8%±25.1% vs. 44.6%±21.5%, P=0.997). Overall, the Strong pre-CRA group did not show a more significant increase in antibody responses to the S protein linear peptides before and after vaccine immunization compared with the Weak pre-CRA group. Therefore, there is no evidence showing a significant impact of pre-existing antibody responses on inactivated vaccine-induced neutralization and antibody responses. Our research provides an important basis for use of inactivated COVID-19 vaccines in the context of high sCoV seroprevalence.